(3GdcTGa Yf MbGFb GdJfRjds - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s ((3MSjf Hf eMeO Hf TQa GdOjf Hf GdMSf QLeGf s)
(3ChdgG (B:s
(3GdMeO dgd GdPi CfRd GdbQBf cdGekG eDdakG efXekG hdbO QCjJ ENhGffG ai GdOjf cdehG QLYhG Edi JaSjQ BjI , aCHQRJ dge HYV GdMbGFb ef GdMLH MJi ELJeYhG Zdi ebJQMjf Cf Cedi Ydjge ai GdcTa Yf MbGFb GdJfRjd s
(3BNQgG (B:s
(3BNQg BNQ JaSjQ ShQI Gdcga s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYfGjI eMeO Hf CMeO Hf YHO GdQGRb GdYdais
(3YdjgG eWGdYI hJUMjM CMeO Hf bGSe GdefaPi s
(3YdjgG JedcGJ CbOegG HGdhQGKI HfJ gGOi Hf MSf GdYdai SfI (B1074(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJaSjQ hYdhe GdbQBfs